Educação, alimentação e saúde infantil : um estudo do Tratado de Educação Física dos Meninos para Uso da Nação Portuguesa (1790) - Troian, Eduarda (Universidade do Vale do Rio dos Sinos, 2023)
This Masters’ Degree Dissertation proposes to analyze the book Treaty on Physical Education for Boys for use by the Portuguese Nation from 1790, written by Francisco de Mello Franco, Portuguese-Brazilian doctor, considering its objective of contributing to the children’s health in the seven hundred’s Portugal, especially concerning the health of children from the male gender. Therefore, we seek to analyze this medicine’s work which, by the influence of the enlightenment movement current in the Portuguese society from the second half of the 18th century, dialogued with the pedagogical proposals which contributed to the children’s development. This book, which characterizes by focusing on the care demanded by the children from the 18th century, had as objective to reach the Portuguese families, especially mothers, for whom the author directed some of his advertences. This way, the book would have been one of the first to approach specific care for the raising and education of healthy boys on the Portugal’s kingdom. Over its 12 chapters, the author approaches the development of the child, contemplating form cares to be observed during pregnancy to the practice of physical exercises. Among the cares, stand out those related to the child’s food, highlighting its importance to the constitution of healthier individuals. To meet the proposed objectives, we work with a bibliographical and a theoretical framework that cover different areas of the History discipline, especially the History of Medicine, Health and Diseases, History of Food, Education and the Social History of Childhood.
Keywords: História da infância; Tratado médico; Receita; Nutrição; Século XVIII; History of childhood; Medical treaty; Prescription; Nutrition; 18th century; ACCNPQ::Ciências Humanas::História